(untitled) (American Journal of Islam and Society, 1999)
This article has multiple objectives. It seeks to identify those assumptions of neoclassical economics which are vindicated by experimental tests and those which fail such tests. The author tries to simultaneously expose the limitations of neoclassical economics and Islamic economics by pointing out that some assumptions of the rational choice model fail while others, often ignored by Islamic economists, are proven valid. The article also seeks to summarize the results of experimental testing about agent behavior under a controlled environment. The author hopes that this initiative will encourage Islamic economists to use experimental methods as a means for testing their theoretical assumptions. The author concludes that human agents are neither as self-regarding as the homo economicus model predicts nor are they as other-regarding as the model homo Islamicus predicts.